Nutrition intake among the Japanese elderly: an intergenerational comparison based on national health and nutrition survey scores - Yuta Yokoyama; Masako Sasaki; Kanae Sato (Taylor & Francis Group, 2019)
Context: The average Japanese lifespan became the longest in the world in 1986. What factors give the Japanese this longevity? Washoku, or the traditional Japanese diet, is respected globally for its nutritionally-balanced and healthy eating habits. This uniquely Japanese way of eating may be one factor that helps extend the Japanese lifespan. Objective: To explain the nutrition intake characteristics of today's Japanese elderly compared with their children's generation and to discuss the association between nutrition intake and various diseases and health issues in the general adult population. Methods: This study compared the characteristics of nutrition status and nutrition intake among today's elderly and their children's generation by using National Health and Nutrition Survey scores. Results: Japanese elderly had high adequacy in all nutrients as well as a high intake of potatoes, pulses, vegetables, fruits, algae, and fish and shellfish compared with their children's generation. Conclusion: Nutrition intake among the Japanese elderly had the characteristics of washoku, but these characteristics were not passed on to the next generation. Extension of the average lifespan and improved health could be achieved by modifying nutrition intake, even after reaching the age of onset of lifestyle- and age-related diseases, typically the 50s.